Quality Management: the Challenges of Regional Governance in West Africa - (:unkn) unknown (My University, 2015)
With a total area of 3 509 600 km2 and a population of over 80 340 000 people, the eight WAEMU countries (the West Africa Economic and Monetary Union) have many products to offer the international market. These products can be classified into three categories: fishery products, agricultural products, and agro-industrial products resulting from the processing in the first two categories. Despite the real independence of these categories, they share a common thread: efficient quality management. The crux of the matter is efficient quality management which denotes both effective and efficient management of the products. While all the theories of efficiency acknowledge a border between effectiveness and efficiency and highlight the complementarity of the two concepts, it is nonetheless interesting to note that the Russian language combines the two concepts into a single word: “effectivnost”. The efficiency of a quality infrastructure is determined by both its effectiveness and its efficiency since a quality product is one that meets the standards in place, has a number of inherent characteristics that fulfil stated requirements, and can be sold within budget limits set by the consumer. In other words, quality must be managed at a restricted cost so that it is not a source of increased production costs. The formal ratification of the SOAMET (West African Secretariat of Metrology), the NORMCERQ (Regional Body of Standardization, Certification and Quality Promotion) and the SOAC (Regional Body of Accreditation) by the eight WAEMU countries through the signing of Regulation No. 01/2005/CM/UEMOA (Scheme for the Harmonization of the Activities of Accreditation, Certification, Standardization and Metrology in the WAEMU) is a very positive step. Nevertheless, both the successful implementation of this regulation and the quality of work that will derive from these organizations depend on the quality of the human factor, i.e. the competence of the people
Keywords: African Research